Cost-effectiveness analysis of the SAPIEN 3 TAVI valve compared with surgery in intermediate-risk patients. (3rd April 2019) - Goodall, Gordon; Lamotte, Mark; Ramos, Mafalda; Maunoury, Franck; Pejchalova, Barbora; de Pouvourville, Gerard
Abstract: Objective: Transcatheter aortic valve implantation (TAVI) has become the therapy of choice for treating severe aortic stenosis in patients at high-risk for surgery or where it is considered too risky to attempt. This uptake varies across geographies however, and its cost or value has frequently been cited as the reason for this. We sought to evaluate the potential cost and clinical impact of TAVI in intermediate risk patients from a French collective perspective. Materials and methods: The analysis was performed using a novel Markov model with data derived from the PARTNER II randomized controlled trial for survival, clinical event rates, and quality-of-life. The simulated time horizon was 15 years, costs were from French sources and presented in 2016 Euros. Discounting of all outcomes was at 4% annually and the effect of uncertainty in model parameters was explored by deterministic and probabilistic sensitivity analysis (PSA). Results: In comparison to surgery, TAVI resulted in improved clinical outcomes (life expectancy and quality-adjusted life expectancy) and lower costs over a lifetime time horizon. The base case results showed increases of 0.42 years and 0.41 QALYs with lifetime cost savings of €439 for TAVI compared to surgery. PSA results showed a >50% likelihood of cost-effectiveness at €0 willingness-to-pay and a 100% likelihood at ∼€15, 000. Limitations: Clinically, survival projections are based on limited follow-up data and introduce uncertainty into the outcomes from the model. Economically, procedure costs are derived from a heterogeneous mix of patient risk groups, although this is much more likely to bias against TAVI and under-estimate overall cost savings. Conclusions: In our analyses of intermediate risk patients, TAVI is associated with superior clinical outcomes compared to surgery and is cost saving. It could be expected that cost savings are conservative and likely to increase over time.